Structural and legal analysis of banking safety in Ukraine - Dzhafarova, O. V.; Джафарова, О. В.; Riabchenko, О. P.; Рябченко, О. П.; Artemenko, І.; Джафарова Олена В'ячеславівна (Baltic Journal of Economic Studies. – 2018. – Vol. 4, № 5. – Р. 64-74, 2018)
Стаття присвячена науковому аналізу економічної діяльності України в умовах європейських інтеграційних процесів. Підкреслюється, що цінність поточної економічної діяльності визначається насамперед процесами глобалізації, формування ринкових відносин, необхідністю створення гарантій в цих умовах, що забезпечить гідне життя всіх членів суспільства через необхідність забезпечення економічної та загальної національної безпеки України. Метою статті є з'ясування концепції банківської безпеки, її основних компонентів та рівнів розвитку. Проаналізовано дані звітів Фонду гарантування вкладів фізичних осіб та Генерального прокурора України за останні роки. Встановлено, що показники ФГВФО не відповідають показникам звітів Генерального прокурора України щодо злочинів, скоєних у сфері банківської справи.

The article is devoted to the scientific analysis of Ukraine’s economic activity under the conditions of European integration processes. It is stressed that the value of the current economic activity is primarily determined by the processes of globalization, the formation of market relations, need for creation of guarantees in these conditions that will ensure a decent life for all members of society because of the need for ensuring the economic and overall national security of Ukraine. However, it is necessary to consider that the access to world markets and formation of an open economy also mean an internal stability of the economy and financial system of the state. The purpose of the article is to clarify the concept of banking security, its main components and levels of development. The report data of the Deposit Guarantee Fund (DGF) and the Prosecutor General’s Office of Ukraine for the last years have been analysed. It also testifies about the lack of control and superficial attitude of the controlling bodies towards the processes of the banking sphere criminalization. It is determined that the DGF indicators do not correspond to those of the Prosecutor General’s Office of Ukraine reports regarding the crimes committed in the sphere of banking. The government of Ukraine should focus on domestic reforms, the creation of living standards, economics and politics in Ukraine, which are as close as possible to European. Only then it is possible to implement effective mechanisms aimed at neutralizing, minimizing the impact and eliminating the phenomena and factors leading to the creation of external and internal threats to the state’s financial security.

Статья посвящена научному анализу экономической деятельности Украины в условиях европейских интеграционных процессов. Подчеркивается, что ценность текущей экономической деятельности определяется прежде всего процессами глобализации, формирования рыночных отношений, необходимостью создания гарантий в этих условиях, что обеспечит достойную жизнь всех членов общества из-за необходимости обеспечения экономической и общей национальной безопасности Украины. Целью статьи является выяснение концепции банковской безопасности, ее основных компонентов и уровней развития. Проанализированы данные отчетов Фонда гарантирования вкладов физических лиц и Генерального прокурора Украины за последние годы. Установлено, что показатели ФГВФЛ не соответствуют показателям отчетов Генерального прокурора Украины о преступлениях, совершенных в сфере банковского дела.
Keywords: banking activity; banking security; state; economic activities; world-economy; economic legislation; economic transformation; integration; globalization; publikatsii u WoS; publikatsii u zarubizhnomu vydanni; economy; банківська безпека; банковская безопасность; Наукові публікації. Scientific publications. Научные публикации; Україна. Ukraine. Украина; Фінансове право. Бюджетне право. Банківське право. Financis Law. Budget Law. Banking Law. Финансовое право. Бюджетное право. Банковское право; Господарське право. Business Law. Хозяйственное право; банківська діяльність; держава; економіка; економічна діяльність; світова економіка; економічне законодавство; економічні перетворення; інтеграція; глобалізація; банковская деятельность; государство; экономика; экономическая деятельность; мировая экономика; экономическое законодательство; экономические преобразования; интеграция; глобализация